Music and cognitive stimulation influence idea generation. (January 2016) - Gültepe, Bedirhan; Coskun, Hamit
Although previous studies have reported that positive affect is associated with enhanced creativity, there are no studies examining the influences of music and cognitive stimulation on brainstorming performance. The purpose of the present study was to examine the effects of music and cognitive stimulation on creativity. Participants in the positive affect condition listened to Vivaldi's Spring, whereas those in the negative affect condition listened to Gyorgy Ligeti's Lux Aeterna . Additionally, individuals in the neutral affect condition listened to Chopin's Waltzes (MacDonald & Davey, 2005; Startup & Davey, 2001). Subsequently, the participants brainstormed the advantages and/or disadvantages of having an extra thumb on each hand. During the brainstorming session, participants were exposed to eight words, including both high-stimulating (e.g., scissors, gloves, etc.) and non-stimulating (e.g., giraffe, lion, etc.) words. There was also a mixed or low stimulation condition comprising four stimulating and four non-stimulating words. The results showed that positive and negative affect enhanced idea generation in the low stimulation condition, whereas neutral affect increased the number of ideas in the high stimulation condition.